The Role of Bacterial Vaginosis in Infection After Major Gynecologic Surgery - L. Lin; J. Song; N. Kimber; S. Shott; J. Tangora; A. Aroutcheva; M. B. Mazees; A. Wells; A. Cohen; S. Faro (Hindawi Limited, 1999)
Purpose: Previous studies have reported an association between bacterial vaginosis (BV) and postoperative fever and infection. This prospective study investigated whether the intermediate or definite stages of BV are risk factors for postoperative infection after major gynecologic surgery.